#TITLE_ALTERNATIVE# - SULAIMAN NUR UBAY (NIM 13304067), MUHAMMAD
Water Dynamics and vapour in boiler has the character of non linear and show shrink and swell phenomenon. The fluctuation in the steam drum boiler PT. XYZ has many effects. Because of that, a control system is needed in order to make the controlled system with a good response, to have a good disturbance rejection, and to track reference trajectory or the set point. Model Predictive Control (MPC) is a technique to bring system to the controlled system to the optimal condition. In this final project, AIDA software is used to perform the modeling based on identification method and SMOC software is used to design predictive controller. Model validation use F-statistic assign steam flow value 1.191 and 0.633 for level indicator controller, show that the model qualified based on F-Statistic with residue less than 0.5. This simulaton show that the respon transien have 3 minute delay, 26 minute settling time and 2% overshoot.